Detection of different degree traumatic vertebral bone marrow oedema by virtual non-calcium technique of dual-source dual-energy CT. Issue 2 (February 2020) - Wang, Y.; Chen, Y.; Zheng, H.; Huang, X.; Shan, C.; Bao, Y.
Abstract : AIM: To evaluate the diagnostic performance of dual-energy computed tomography (DECT) using the virtual non-calcium (VNCa) technique for the detection of different degrees of vertebral bone marrow oedema. MATERIALS AND METHODS: The present prospective study was approved by the institutional ethics committee. Informed consent was obtained from all patients. Twenty patients underwent both DECT and MRI. Vertebral bodies on VNCa images were graded visually by two blinded, independent radiologists using a three-point classification system (0=normal bone marrow, 2=distinct abnormal bone marrow attenuation). DECT values obtained from VNCa images were calculated by a third radiologist. Vertebral bodies on MRI images were graded by a forth radiologist using the same classification as DECT; magnetic resonance imaging (MRI) served as the reference standard. RESULTS: The agreement between VNCa and MRI images for the grading of bone marrow oedema was substantial (κ=0.694). If MRI at grade 2 was regarded as positive for bone marrow oedema, VNCa images achieved an overall sensitivity of 85%, specificity of 97.5%, positive predictive value of 81%, negative predictive value of 98.1%. Receiver operating characteristic analysis based on CT values for the diagnosis of distinct bone marrow oedema revealed an area under the curve of 0.950. A cut-off value of –11.80 HU provided a sensitivity of 95% and specificity of 86.3% for the diagnosis of distinct bone marrow oedema at DECT. CONCLUSION: DECT images of VNCa showed excellent diagnostic performance for the detection of distinct vertebral bone marrow oedema. Highlights: VNCa technique of DECT allows for detecting different degrees of bone marrow oedema in vertebral compression fractures.